Harmonisasi Equidistance Line Principle Danmedia Line Prinsiple dalam Penentuan Batas Wilayah Laut - Ria Tri Vinata (Faculty of Law Hang Tuah University, 2017)
Determination of maritime boundaries using the median line or equidistance principle for maritime boundary disputes also considers other factors outside the distance factor. The concept of relevant circumstances is closely related to the principle of equity. In determining the boundary sea boundary boundaries are not bound by strict legal norms to balance all inherent conditions to find fair results. There are many relevant situations related to geographic and non geographical factors, the application of Equidistance Line with relevant circumstances. This is a legal approach to delimitation of sea boundaries. However, in the practice of the country in the 19th and early 20th centuries for the determination of sea territorial boundaries, especially for territorial sea, namely the median line, thalweg line, perpendicular line, and prolongation of the land boundary, the median line is the most widely applied method by the state. other countries in determining the territorial sea boundaries.